Annulation cascade of arylnitriles with alkynes to stable delocalized PAH carbocations via intramolecular rhodium migration. Issue 24 (6th June 2018) - Yin, Jiangliang; Zhou, Fulin; Zhu, Lei; Yang, Mufan; Lan, Yu; You, Jingsong
Abstract : An annulation cascade of arylnitriles with alkynes is disclosed to provide stable delocalized carbocations with the ability to specifically target lysosomes. Abstract : Herein, we propose the conception of heteroatom-promoted delocalization of the positive charge of an oxonium ion and thus develop a highly efficient rhodium(iii )-catalyzed hydration and three fold C–H activation/annulation cascade of arylnitriles with alkynes, affording a structurally diverse family of delocalized polycyclic aromatic hydrocarbon (PAH) carbocations. DFT calculations demonstrate that the positive charge mostly locates around the C1 atom and is partly delocalized by ambient N, O1 and C5 atoms. A mechanistic study indicates that the hydration of the arylnitrile and three fold insertion of the alkyne is a successive process rather than a step by step process, wherein a unique intramolecular rhodium migration is probably involved. These novel carbeniums show tunable fluorescence emission, low cytotoxicity and the ability to specifically target lysosomes.